The Effectiveness of Digital Pop-Up Book Media on Learning Achievement in Pancasila Education among Third-Grade Students at SD Negeri 1 Padokan, Bantul Regency - Nugroho, Irfan Adi; Chairiyah; Azkiyah, Lailatul; Nofridha, Eka Ridha; Megawati, Ida (CV. Kurnia Grup, 2025)
This study aims to (1) determine how much the tendency of Pancasila Education learning achievement in class III taught using Pop Up Book Digital media and Interactive PowerPoint media, (2) determine the difference in Pancasila Education learning achievement between learning using Pop Up Book Digital media and Interactive PowerPoint media. This research uses a quantitative approach with the Quasi Experimental Design method. The population taken was third grade students of SD Negeri 1 Padokan, totaling 56 students. The sampling technique used a census / total sampling where class III A as an experimental class and class III B as a control class. Data collection techniques used observation, interviews, tests, and documents. The data analysis technique used descriptive analysis and prerequisite test analysis which included normality test, homogeneity test, hypothesis testing using t-test, and N-Gain test. The results showed (1) the increase in learning achievement of Pancasila Education was higher which was taught using Pop Up Book Digital media. This is evidenced by the average posttest score, for the experimental class of 82.68 and the control class of 77.14; (2) there are differences in learning achievement of Pancasila Education in class III. This is evidenced by the significance value (2-tailed) of 0.048 <0.050. The conclusion of this study is that there is an increase in learning achievement of Pancasila Education before and after being given a treatment.